Muslim Americans : debating the notions of American and un-American - Kabir, Nahid Afrose (London ; New York, NY : Routledge/Taylor & Francis Group, 2018)
"With Islamophobia on the rise in the US rise since 9/11, Muslims remain the most misunderstood people in American society. Taking as its point of departure the question of the compatibility of Islam and democracy, this book examines Muslims' sense of belonging in American society. Based on extensive interview data across seven states in the US, the author explores the question of what it means to be American or un-American amongst Muslims, offering insights into common views of community, culture and wider society. Through a combination of interviewees' responses and discourse analysis of print media, Muslim Americans also raises the question of whether media coverage of the issue might itself be considered 'un-American.' An empirically grounded study of race and faith-based relations, this book undertakes a rigorous questioning of what it means to be American in the contemporary US. As such, it will appeal to scholars of sociology and political science with interests in race, ethnicity, religion and national identity"--Provided by publisher.
Introduction: The "Muslim question" continues -- What does it mean to be an American or un-American? -- Culture matters -- Is the media "un-American"? -- Modern-day McCarthyism -- Conclusion: Comprehending the present and looking into the future.
Includes bibliographical references (pages [219]-224) and index.
ENH
Trim Education
Keywords: Muslims -- United States -- Social conditions; Muslims -- United States -- Ethnic identity; Muslims -- Cultural assimilation -- United States; National characteristics, American -- Social aspects; Muslims -- United States -- Interviews; Ethnicity -- Social aspects -- United States; Ethnicity -- Political aspects -- United States; Islam -- Social aspects -- United States; Islam and politics -- United States; English language; United States -- Ethnic relations